2020
DOI: 10.1039/d0ra05813k
|View full text |Cite
|
Sign up to set email alerts
|

Ratiometric electrochemical sensor for accurate detection of salicylic acid in leaves of living plants

Abstract: This is the first report on developing a ratiometric electrochemical sensor for detecting SA in the leaves of living plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The modification of GO can make it have the ability to form chemical bonds with PCM systems [35,36]. Pielichowska et al [37] prepared polyurethane-based PCMs containing polyethylene glycol fragments with an average molar mass of 8000 g/mol, and found that the phase change heat and crystallinity of the 0.3% graphite nanosheet modified system were the highest in polyurethane without chain extender.…”
Section: Introductionmentioning
confidence: 99%
“…The modification of GO can make it have the ability to form chemical bonds with PCM systems [35,36]. Pielichowska et al [37] prepared polyurethane-based PCMs containing polyethylene glycol fragments with an average molar mass of 8000 g/mol, and found that the phase change heat and crystallinity of the 0.3% graphite nanosheet modified system were the highest in polyurethane without chain extender.…”
Section: Introductionmentioning
confidence: 99%
“…Although flexible electrochemical sensors have been reported in the literature for monitoring phytohormones 44 47 , the research field is still in its infancy and little to no research has been conducted on developing an integrated hybrid sensing system for real-time quantification of volatile and liquid phytohormones and VPD levels along with the radial growth of stem for early diagnosis of crop stress. This work reports the first-of-its-kind integrated, flexible, and multiparametric sensor suite that enables continuous and non-destructive monitoring of a plant’s physiology with spatiotemporal fidelity.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Although simple colorimetric tests were developed using metal salts such as ferric chloride, [5] such methods lack sensitivity or specificity. Some recent work also used electrochemistry, [6] and surfaceenhanced Raman spectroscopy. [7] These methods rely on the intrinsic redox and molecular vibrational properties of SA, and are susceptible to interference in complex sample matrix.…”
Section: Introductionmentioning
confidence: 99%